2018
DOI: 10.1002/anie.201806386
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering Metal‐Free Polymeric Carbon Nitride Electrocatalyst for Effective Nitrogen Fixation under Ambient Conditions

Abstract: Electrocatalytic nitrogen reduction reaction (NRR) under ambient conditions provides an intriguing picture for the conversion of N into NH . However, electrocatalytic NRR mainly relies on metal-based catalysts, and it remains a grand challenge in enabling effective N activation on metal-free catalysts. Here we report a defect engineering strategy to realize effective NRR performance (NH yield: 8.09 μg h mg , Faradaic efficiency: 11.59 %) on metal-free polymeric carbon nitride (PCN) catalyst. Illustrated by den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
378
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(412 citation statements)
references
References 42 publications
14
378
0
1
Order By: Relevance
“…Due to the wide application in agriculture and chemical industry, ammonia has enormous global demand . Most synthetic ammonia is produced by the Haber–Bosch process that is conducted at harsh conditions (400–500 °C and 150–250 atm) and consumes a large amount of energy . Inspired by the biological nitrogen fixation, the electrochemical nitrogen reduction reaction (NRR) is considered to be an economic and environmentally friendly alternative for the Haber–Bosch process.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide application in agriculture and chemical industry, ammonia has enormous global demand . Most synthetic ammonia is produced by the Haber–Bosch process that is conducted at harsh conditions (400–500 °C and 150–250 atm) and consumes a large amount of energy . Inspired by the biological nitrogen fixation, the electrochemical nitrogen reduction reaction (NRR) is considered to be an economic and environmentally friendly alternative for the Haber–Bosch process.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] To this end, the search for an electrocatalytic NRR center in recent years has mainly focused on transition-metal-based materials. [27][28][29][30][31] Fore xample, Yu et al reported ah igh NH 3 production rate and faradaic efficiency by using boron-doped graphene as am etal-free NRR catalyst under ambient conditions. [7] It is worthwhile to note that although an unoccupied nonbonding orbital and electron donor site with abundant electron cloud density are prerequisites for aN RR catalyst, the do rbital electrons in transition metals also benefit the formation of metal-hydrogen bonds,w hich will exacerbate the competitive hydrogen evolution reaction and limit the nitrogen reduction selectivity and catalytic efficiency.…”
mentioning
confidence: 99%
“…[24] Compared to transition metals,t he weak hydrogen adsorption of nonmetallic elements and their abundant valence electrons should provide am ore ideal nitrogen activation center. [27][28][29][30][31] Fore xample, Yu et al reported ah igh NH 3 production rate and faradaic efficiency by using boron-doped graphene as am etal-free NRR catalyst under ambient conditions. [27][28][29][30][31] Fore xample, Yu et al reported ah igh NH 3 production rate and faradaic efficiency by using boron-doped graphene as am etal-free NRR catalyst under ambient conditions.…”
mentioning
confidence: 99%
“…e) Metal‐free polymeric carbon nitride with defects for NRR. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%
“…In particular, N vacancies were deliberately engineered in polymeric carbon nitride. A significantly enhanced activity was obtained via end‐on binding of dinitrogen in these vacancies, which increased the bond length and promoted spatial electron transfer . It is strongly recommended that isotopic labeling experiment using 15 N 2 feed gas should be done to determine the mechanism of NRR in N‐containing electrocatalysts.…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%